Tax Structure and Developing Countries - Thaçi, Lumnije; Gërxhaliu, Arbnora (European Journal of Economics and Business Studies, 2018)
The main source of public revenue compared to other sources are Taxes, as in developed countries and developing countries, therefore the tax system has an extraordinary role in sustainable economic development and employment growth. Also, tax policy that acts in a complementary way to monetary policy is of vital importance also due to the preservation of economic stability by limiting the level of inflation and balancing the equilibrium on the market. The main purpose of this paper is to explore the tax structure in developing countries and their comparison with developed countries. In this paper some tax theory will be discussed. It will also be shown for impractical research and their effects on economic development and the growth of social welfare. Although there is no consensus among researchers, most empirical studies show a negative link between public spending and economic growth. However, in order for the tax effects to be the highest in the economy in developing countries, the international trade tax and the VAT should be replaced rather within the country.
Keywords: . Structure of taxes, direct taxes, indirect taxes, developing countries, economic development.